Takotsubo Cardiomyopathy Mimicking Stent Thrombosis After Percutaneous Coronary Intervention - Furqan Khattak MD; Muhammad Khalid MD; Ghulam Murtaza MD; Timir K. Paul MD, PhD (SAGE Publishing, 2018)
Takotsubo cardiomyopathy, also known as "broken heart syndrome," is a transient left ventricular dysfunction associated with stress (usually emotional) induced myocardial injury and stunning. It often presents as myocardial infarction on surface electrocardiogram (EKG). Diagnosis is made by coronary angiography, which rules out coronary artery disease and shows pathognomonic apical ballooning. In this article, we present a case of a 72-year-old woman who initially presented with an ST segment elevation myocardial infarction on EKG. Coronary angiography showed severe left anterior descending artery and diagonal lesions requiring percutaneous coronary intervention. Post-percutaneous coronary intervention, EKG changes resolved. The next day, the patient developed recurrent chest pain and her EKG showed diffuse T-wave inversion in precordial leads with reemerging ST segment elevations concerning for stent thrombosis. The patient underwent repeat emergent coronary angiography, which showed patent stents and findings consistent with takotsubo cardiomyopathy.